Comparing theories to explain exercise behaviour: a socio-cognitive approach - Wee Yu Ghee; Yap Sheau-Fen; Md. Nor Othman (2013)
Consumer education plays an important role in cultivating the beliefs that exercise helps to improve one’s health status. In this vein, a solid theoretical model that provides insight into what motivates exercise participation is essential for managerial formulation of health intervention strategies. Addressing the calls for more solid theoretical work to explain exercise behaviour, this study tests and compares empirically the predictive validity of three social cognitive theories – the theory of reasoned action, the theory of planned behaviour (TPB) and the modiﬁed TPB (with an additional path from subjective norms to attitude) – in predicting exercise intention. Cross-sectional data were collected via self-administered surveys from a sample of adults in Malaysia. All three alternative models have achieved acceptable model ﬁt to the data, and the TPB appeared to be more superior to the alternative models. Given strong support for the second-order TPB’s application to exercise that is provided by our study, it seems feasible that desirable modiﬁcations in social cognitions especially the attitudinal components might lead to corresponding changes in the subjects’ exercise intention. This study sets the ground for health professional, social marketers and government to improve their understanding of exercise behaviour and, in turn, consumer welfare.